Genomic stability and tumorigenesis. - Sieber, O; Heinimann, K; Tomlinson, I (2005)
Cancer research needs to explain the observed incidence of cancer. Many factors determine this process, including: the number of susceptible cells in the tissue of origin; the number of normal cell divisions through which susceptible cells pass in normal development and turnover; the number of cell divisions during tumorigenesis; the selective advantage which tumour cells have acquired; the ease of detection of a cancer; the number of mutations which are required for malignancy; the possible stepwise nature of tumorigenesis; the value of the normal mutation rate; the presence of extrinsic factors such as mutagens or growth promoters; the presence and strength of genomic instability, a phenomenon which has received a great deal of attention. We know very little about most of the factors and their influence in humans. We cannot, therefore, readily answer the question as to whether or not the observed incidence of cancer is what we would expect. Specifically, it is not yet possible to assess whether or not genomic instability is a prerequisite for carcinogenesis. Mathematical models, which assess the importance of genomic instability in tumorigenesis can be helpful, but require interpretation in the context of our overall ignorance. Experimental data have shown genomic instability in some cancers, but we do not yet know whether or not hypermutation initiates and drives tumorigenesis.